The effect of problem-based learning model assisted by tiktok videos on students' cognitive learning outcomes at SMPN 22 Padang - Rani Anggraini; Rani Oktavia (SEMESTA: Journal of Science Education and Teaching, 2026)
This study used a quasi-experimental design with a nonequivalent control group design to examine the effect of the Problem-Based Learning (PBL) model assisted by TikTok videos on students’ cognitive learning outcomes in ecology and biodiversity topics. The study was conducted with seventh-grade students at SMP Negeri 22 Padang using a quantitative approach. The sample consisted of two classes selected through purposive sampling, with class VII.A as the experimental group and class VII.B as the control group. Data were collected using a 20-item multiple-choice test administered before (pretest) and after (posttest) the intervention. The results showed that the average posttest score of the experimental group (79.69) was higher than that of the control group (65.78), with a t-value of 4.10 exceeding the t-table value of 2.00 at a significance level of 0.05. These findings indicate that the implementation of the PBL model assisted by TikTok videos has a significant effect on improving students’ cognitive learning outcomes. The integration of problem-based learning activities with short video media provides a more engaging, interactive, and contextual learning experience in science education.